Photobiomodulation in fibroblasts: from light to healing through molecular pathways, omics and artificial intelligence - Ucci, Sarassunta; Caradonna, Eugenio; Aliberti, Anna; Cusano, Andrea (Frontiers in Bioengineering and Biotechnology, 2025)
Photobiomodulation (PBM), a non-invasive therapy that uses non-ionizing light in the visible to near-infrared spectrum, has proven to be a promising strategy for promoting tissue repair and regeneration. PBM has its roots in heliotherapy and low level light therapies and works by activating specific molecular pathways in the target cells. Among these, fibroblasts play a central role in mediating wound healing responses. This article provides a comprehensive overview of the mechanisms of action of PBM, focusing on the effects on fibroblast biology, including modulation of proliferation, migration and extracellular matrix remodeling. Recent advances in omics technologies and artificial intelligence (AI) provide new tools to unravel the complexity of PBM-induced signaling and optimize therapeutic protocols. By integrating data-rich approaches and systems-level analysis, this work highlights the potential of PBM as a precision-guided regenerative modality and underscores the need for further translational studies to support its clinical application.